The Effect of 'Green' Messages on Brand Purchase and Brand Rejection. Issue 2 (May 2013) - Wheeler, Meagan; Sharp, Anne; Nenycz-Thiel, Magda
The paper considers consumer brand rejection of 'green' and non-green brands. We find empirically that 'green' brands are not considered largely because they are unfamiliar, rather than being consciously rejected. Consumers do not think about these brands in a buying situation, suggesting that their single 'green' message is not enough to make it into the shoppers' consideration set. Additionally, not being 'green' was not a reason for rejection of non-green brands. These findings highlight the importance of brand advertising to build multiple, relevant memory structures for any brand, thereby increasing the probability of being thought of during a buying occasion.